Hospital de Pediatria da UFRN: resgatando memórias na construção da história - Oliveira, Selma Suely Silva (2007)
This study deals with a historical, descriptive and exploratory approach aiming to recall the origin and trajectory of the Pediatrics Hospital at Universidade Federal do Rio Grande do Norte. This research also deals with the insertion of the nursing department in the same Hospital. This was realized through existing records and discourse collected through interview of professionals-doctors, nurses, midwifes, nursing attendants and psychologists. Thus, a network was established and consisted of qualified informants, composed through reference analysis. Data treatment and analysis was performed based on the collection of oral data. The data was considered according to the font s context, all of which depending on process of comprehension and interpretation. The research was based on the main theme, through oral history used in order to build a historical background. These main themes were then subdivided and other discourses were made present such as: the historical scene, the dream came true and the insertion of nursing, present in the history construction; all of which enabled the research. Thus, in this process, it was possible to identify the most important characters of the origin of children s health services organization and assistance at Rio Grande do Norte. It was possible to perceive that this institution aimed to initiate health services that dealt with an education for future generations. This was observed through the creation of the Faculty of Medicine of Natal and as a consequence, the installation of a Pediatrics Hospital that dealt with medical education. The research made evident that the nursing contributed for a structuring of quality health assistance towards children, even though the resources and working conditions were scarce, extensive work shifts and low professional qualification. It was observed that the there was change in the category s profile, once nurses were introduced in the service. Once this happened, changes in mentality, and innovative processes as well as professional conducts were established. The distinctive relation between acting and doing of doctors and nurses were also dealt with. Thus, the first item is done towards the idealization, projection and prescription. The second issue deals with concretization in realization of something that was not projected and realized, causing suffering and unsatisfaction. At the end, it was possible to confirm that oral history is a very rich element and it is possible through subjects that build history, through their perceptation of the facts and the context in that their are inside